Reanalysis of the Ångström System (B1Σ+ - A1Π) in the 13C16O Isotopic Molecule. - Hakalla, Rafał; Szajna, Wojciech; Zachwieja, Mirosław; Kępa, Ryszard (Polish Academy of Sciences, Institute of Physics (Acta Physica Polonica A), 2012)
The emission spectrum of the Ångström system (B 1 Σ+-A 1π) of 13C 16O was obtained under high resolution with an accuracy estimated to be ±0:002 cm -1 as an emission spectrum using a high accuracy dispersive optical spectroscopy. The light source was a hollow-cathode lamp with two anodes built in our laboratory, with a previously deposited small quantity of 13C carbon on the electrodes. The emission from the discharge was observed with a plane grating spectrograph and recorded by a photomultiplier tube. In total 195 transition wave numbers belonging to the strongest 0-1 and 0-2 bands of the B-A system were precisely measured. The modern rotational reanalysis made it possible to verify the molecular information for the both combining states of the Ångström system. In particular the rovibrational constants for the B 1Σ + Rydberg state have been significantly improved (B0 = 1:8625054(65) cm -1 and D 0 = 6:1384(52) × 10 -6 cm -1) and the obtained equilibrium rotational constants of this state are more accurate than known to date. Numerous rotational perturbations observed in the A 1π state were reanalysed and confronted with the previously known ones.
Keywords: High resolution molecular spectroscopy; carbon monoxide; Angström system; (B1Σ+-A1π); 13C16O isotopologue